Coronary slow flow phenomenon and microalbuminuria: Is there any relationship? - Alireza Amirzadegan; Rosa Ghaderpanah; Elham Rayzan; Arya Aminorroaya; Masih Tajdini (KARE Publishing, 2019)
Objective: The pathophysiology of coronary slow flow phenomenon (CSFP) is poorly understood. Evidence suggesting endothelial dysfunction in patients with slow coronary flow (SCF) led to this evaluation of a possible correlation between microalbuminuria (MAU), as an indicator of endothelial dysfunction, and CSFP in order to investigate a mutual pathophysiology. Methods: In this case-control study, 15786 patients who presented between September 2016 and April 2018 were screened. All patients with CSFP had chest pain and coronary angiography was indicated due to a positive noninvasive test. All cases had a Thrombosis in Myocardial Infarction (TIMI) flow grade of 2 or a corrected TIMI frame count of >27 without any evidence of obstructive coronary artery disease. The patients used as controls had completely normal coronary angiograms. Fasting mid-stream urine samples were analyzed using an immunoturbidimetric assay to determine the albumin-creatinine ratio (ACR) as a surrogate of microalbuminuria (MAU) (ACR: 30-300 mg/g). The prevalence of MAU in the case and control groups was analyzed. Results: A total of 154 individuals with a normal coronary angiogram and 46 patients with SCF were enrolled in the study. The prevalence of MAU was greater in patients with SCF than in the control group (8.7% vs 1.9%, respectively; p=0.048). Even after adjustment for major risk factors, the association between MAU and CSPF remained significant. Conclusion: The results of this study indicated that there was a relationship between MAU and CSFP and confirmed that endothelial dysfunction is a contributing factor to CSFP. These findings are of utmost importance due to the prognostic value of MAU for both all-cause and cardiovascular mortality rates.